2019
DOI: 10.9734/jammr/2019/v30i130165
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stigma and Discrimination on Adherence to Medication amongst People Living with HIV in Tiv Land, North Central Nigeria

Abstract: In spite the identification of stigma as a factor impeding public utilisation of HIV counselling, testing, and treatment services in Nigeria, gaps still exist in knowledge on the impact of stigma, and discrimination on adherence to medication amongst people living with HIV (PLWH). This study adopted mixed methods to examine the impact of stigma and discrimination on adherence to medication amongst PLWH in Nigeria.  A sample of 1,621 respondents was collected using multi-stage and purposive sampling methods. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Following ARV testing of blood samples from all participants who tested HIV positive, a high proportion (28.4%) of individuals who self-reported being HIV negative had detectable ARV biomarkers, indicating possible intentional concealment of their HIV-positive status. This is not surprising due to pervasive HIV stigma and discrimination in Nigeria [ 18 20 ] . Additionally, studies have shown HIV-positive individuals may decide to conceal their status, especially in healthcare-related activities such as surveys, due to concerns about breach of confidentiality, fear of denial of quality healthcare, and judgement from healthcare providers [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following ARV testing of blood samples from all participants who tested HIV positive, a high proportion (28.4%) of individuals who self-reported being HIV negative had detectable ARV biomarkers, indicating possible intentional concealment of their HIV-positive status. This is not surprising due to pervasive HIV stigma and discrimination in Nigeria [ 18 20 ] . Additionally, studies have shown HIV-positive individuals may decide to conceal their status, especially in healthcare-related activities such as surveys, due to concerns about breach of confidentiality, fear of denial of quality healthcare, and judgement from healthcare providers [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria specifically and Sub-Saharan Africa in general, the victory over the spread of HIV/AIDS has been very slow due to poverty and its manifestations [10,15,16]. Given these conditions of lack of food among HIV/AIDS patients receiving treatment in low income communities, recuperation period would be longer; thereby hiking the possibility of stigmatisation and tendency to avoid treatment centres where they (HIV patients) would be sighted collecting drugs; they travel longer distances to other drug centres outside their immediate communities, incurring additional burden of high transportation cost leading to inability to replenish exhausted stock of drugs and treatment failure among low income earners [17]. To improve the health outcome of low income HIV patients who are receiving treatment but unable to adequately feed themselves, I suggest that food supplementation should be incorporated into the treatment package.…”
Section: Discussionmentioning
confidence: 99%